Designpedia : 80 tools for realizing your ideas - Gasca, Juan; Zaragozá, Rafael (LID Publishing, 2017)
Understanding the goals of the world of business and dealing with the development of new solutions calls for a basic ingredient: creativity. And yet, just being, or wanting to be creative is not enough - it is essential to train and develop this ability in order to achieve results. In other words, we need a guide to show us the way and provide us with the tools needed to progress. Designpedia is an essential manual for Design Thinking which brings together all the tools you need to achieve innovation and entrepreneurship goals and is organised around four basic processes: mapping, exploring, building and testing. It also reveals how, as long as you use the right tools, you can create original and effective solutions. Includes case studies to show how this is working for big companies (Orange or BBVA) as well as startups (Dovase or Bydsea).